The effect of strength and plyometric training on anaerobic power, explosive power and strength quadriceps femoris muscle in soccer players - Khodajo, A. R.; Nikseresht, A.; Khoshnam, E. (European Journal of Experimental Biology, 2014)
The purpose of the present study was to investigate the effect of 8 weeks of strength and plyometric training on anaerobic power, explosive power and strength quadriceps femoris muscle in Soccer Plcty'ers. 20 male soccer players who aged 20-30 voluntarily participated in the study. They were assigned in strength (n-10) and plyometric (n=10) groups. Both groups performed selected soccer-specified strength and plyometric for 8 weeks. Data was analyzed using paired t-test, independent t-test statistical methods. The results showed that strength Quadriceps femoris muscle statistically significant increase in post-test compared to pre-test in strength training group (p=0.015) and explosive power in statistically significant increase in post-test compared to pre-test in plyometric training gi'oup (p=0.021). Between-groups comparison showed better records in expiosh'e power for plyometric competed with strength training group after eight weeks (p=0.049j. The results showed that both strength and plyometric training improves physical fitness in soccer plcty'ers. Therefore, recommended that both types of training program to prepare their benefit.